2017
DOI: 10.1021/acs.jpclett.7b00524
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Exciton Binding Energy and the Dielectric Constant in Single-Crystal Methylammonium Lead Triiodide Perovskite

Abstract: We have accurately determined the exciton binding energy and reduced mass of single crystals of methylammonium lead tri-iodide using magneto-reflectivity at very high magnetic fields. The single crystal has excellent optical properties with a narrow line width of ∼ 3 meV for the excitonic transitions and a 2s transition which is clearly visible even at zero magnetic field. The exciton binding energy of 16 ± 2 meV in the low temperature orthorhombic phase is almost identical to the value found in polycrystallin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
159
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 45 publications
15
159
0
Order By: Relevance
“…The mixed‐halide CsPbX 3 films (CsPbI 3 , CsPbI 2 Br, and CsPbBr 3 ) were prepared to compare the dependence of the photophysical properties on the halide cage (octahedra network of PbX 6 , X = I, Br). The transmission spectra did not show any structural phase transitions even at extremely low temperature, in contrast to those of the organic counterparts as previously reported ( Figure 13 a, left) 14, 79, 80. It was suggested that the presence of a molecular dipole determines the overall electronic properties of halide perovskites.…”
Section: Photophysical Analysissupporting
confidence: 82%
“…The mixed‐halide CsPbX 3 films (CsPbI 3 , CsPbI 2 Br, and CsPbBr 3 ) were prepared to compare the dependence of the photophysical properties on the halide cage (octahedra network of PbX 6 , X = I, Br). The transmission spectra did not show any structural phase transitions even at extremely low temperature, in contrast to those of the organic counterparts as previously reported ( Figure 13 a, left) 14, 79, 80. It was suggested that the presence of a molecular dipole determines the overall electronic properties of halide perovskites.…”
Section: Photophysical Analysissupporting
confidence: 82%
“…One such example is the possible correlation between dielectric constant and defects for perovskites. Although there are a few works on this including the reports of giant dielectric constant . Work is to be done to separate the effect of ions for more accurate future study of defect studies.…”
Section: Discussionmentioning
confidence: 99%
“…It also promotes the understanding of the nature of the hysteresis loop in the J−V curve, facilitating to gain insight into, among others, the transient capacitive current, trapping and detrapping process, ion migration, and ferroelectric polarization, thus a useful tool for determining the power conversion efficiency of any newly discovered perovskite material . Determinations of exciton binding energies, electron‐hole diffusion lengths, defect tolerance, effective carrier masses, and strength of bandgap, as well as an understanding of nature of the band structure, density of states spectra, and the interplay of hydrogen bonding and other noncovalent interactions cover a major part of this area of research, thereby advancing the development of our fundamental understanding of the device chemistry and physics of halide based perovskite materials …”
Section: Introductionmentioning
confidence: 99%